Impact of non-financial rewards on employees' job satisfaction / Nur Masriyah Hamzah and Syafawati Matkhairuddin - Hamzah, Nur Masriyah; Matkhairuddin, Syafawati (2023)
Employees serve as a strategic resource for a company, providing a competitive edge through distinct offerings from its staff. Crafting and implementing a rewards program, encompassing non-monetary inducements, becomes somewhat intricate when striving for mutual gains between the employer and the workforce. To sustain the valuable input of employees, the organization must make substantial investments in meeting their requirements via a comprehensive reward structure. This research aims to uncover the influencing factors of non-financial rewards on employee job satisfaction and establish the correlation between non-financial rewards and job satisfaction. The study focused on employees at the Rubber Industry Smallholders Development Authority office in Selangor as its sample group. A total of 40 questionnaires were distributed, resulting in 36 collected responses that were subsequently analysed. Descriptive analysis was carried out using Statistical Package for Social Science version 28. In addition, Pearson correlation and regression analyses were performed to ascertain the connection between the independent and dependent variables. The study's findings indicate that several key factors have a notable impact on employees' job satisfaction. These include receiving formal praise (μ=4.167), understanding employee behaviour (μ=4.028), receiving appropriate recognition (μ=4.000), obtaining continuous feedback (μ=4.000), gaining informal praise (μ=3.944), and frequently receiving recognition from a manager (μ=3.944). Furthermore, the results reveal a strong positive correlation between non-financial rewards and job satisfaction (r (34) = .966, p = .001), thereby supporting hypothesis 1. This suggests that non-financial rewards play a significant role in elevating employees' job satisfaction and potentially enhancing the organisation's overall efficiency. Consequently, the outcomes of this study can serve as a valuable guideline for the RISDA organisation to enhance its reward system, with the potential to fulfil employees' needs and concurrently achieve heightened employee satisfaction.